ATP and ACh Evoked Calcium Transients in the Neonatal Mouse Cochlear and Vestibular Sensory Epithelia - Rabbitt, Richard D.; Holman, Holly A. (Frontiers in Neuroscience, 2021)
Hair cells in the mammalian inner ear sensory epithelia are surrounded by supporting cells which are essential for function of cochlear and vestibular systems. In mice, support cells exhibit spontaneous intracellular Ca2+ transients in both auditory and vestibular organs during the first postnatal week before the onset of hearing. We recorded long lasting (>200ms) Ca2+ transients in cochlear support cells (CSCs) and vestibular support cells (VSCs) in neonatal mice using the genetic calcium indicator GCaMP5. Both CBCs and VSCs exhibited spontaneous intracellular Ca2+ transients, in some cases propagating as waves from the apical (endolymph facing) to the basolateral surface with a speed of ~25µm per second, consistent with inositol trisphosphate (IP3) -dependent calcium induced calcium release (CICR). Acetylcholine (ACh) evoked Ca2+ transients were observed in both IBCs and VSCs, with a larger change in GCaMP5 fluorescence (∆F/F) in VSCs. Adenosine triphosphate (ATP) evoked Ca2+ transients occurred predominantly in Hensen’s cells, Deiters’ cells, inner hair cells, inner phalangeal cells and inner border cells (IBCs). A Ca2+ event initiated in one IBC propagated in some instances longitudinally to neighboring IBCs with an intercellular speed of ~2µm per second and decayed after propagating along ~3 cells. Similar intercellular Ca2+ (GCaMP5G, ∆F/F) propagation was not observed in the radial direction from IBCs to inner sulcus cells and was not observed between adjacent VSCs.